Broadening the Definition of 'Retirement Age' in Old Age Security Benefit Distribution - Hitaningtyas, Ratih Dheviana Puru; M. Hadi Subhan; Nurwahjuni (Arena Hukum, 2025)
The Old Age Security Program has attracted considerable attention within the broader context of social security implementation, particularly due to frequent changes in regulations governing benefit distribution. This article analyses the inclusion of criteria for workers or labourers who have ceased employment as an expansion of the definition of 'retirement age' in relation to beneficiary eligibility under Government Regulation No. 46 of 2015 concerning the Implementation of Old Age Security (Government Regulation No. 46/2015) and its amendments. Under Article 35, paragraph (2) of Law No. 40 of 2004 concerning the National Social Security System (SJSN Law), Old Age Security benefits are provided to participants who retire, experience permanent total disability, or pass away. This analysis differs from previous studies that focused solely on changes to the waiting period for workers or labourers experiencing termination of employment. The research employs statutory, case, and conceptual approaches, and applies grammatical and systematic analysis to legal materials. The findings indicate that, although expanding the definition of 'retirement age' in the implementation regulations does not align with the original intent of the Old Age Security Program as part of the National Social Security System, the Constitutional Court has determined that such expansion is permissible under conditions of force majeure, such as termination of employment. It is recommended that future benefit distribution under the Old Age Security Program realign with the program's foundational principles.